â€œAn Analyze The Effect Of Loan To Deposit Ratio (LDR), Non Performing Loan (NPL), And Loan Interest Rate On Return On Assets (ROA) In Bank Perkreditan Rakyat (Peopleâ€™s Credit Banks) In Indonesia In The Period Of 2010-2014â€ - B01112121, Wiwit Winarni (Jurnal Pembangunan dan Pemerataan, 2016)
This research aims to analyze the effect of Loan to Deposit Ratio (LDR), Non Performing Loan (NPL), and Loan Interest Rate on Return On Assets (ROA) in Bank Perkreditan Rakyat (Peopleâ€™s Credit Banks) in Indonesia in the period of 2010-2014. This research used time series secondary data obtained from the website of Bank Indonesia at the Indonesian Banking Statistics (SPI). The data analysis method used was multiple regression analysis with OLS (Ordinary Last Square). The research finding indicated that Loan to Deposit Ratio had a positive and insignificant effect on Return On Assets with a significance level of 0.8599 > 0.05; Non-Performing Loan had a positive and insignificant effect on Return On Assets with a significance level of 0.4295 > 0.05; and Loan Interest Rate had a positive and insignificant effect on Return On Assets with a significance level of 0.4055 > 0.05. Meanwhile, simultaneously Loan to Deposit Ratio, Non Performing Loan, and Loan Interest Rate had a significant effect on Return On Assets in Bank Perkreditan Rakyat (Peopleâ€™s Credit Banks) in Indonesiain the period of 2010-2014. The determination coeficient showed that in the regression model 14.4 percent of change in the variable of Return On Assets was affected by Loan to Deposit Ratio, Non Performing Loan, and Loan Interest Rate, while the remaining 85.5 percent was affected by other variables or factors that were not covered in this research.Keywords: Loan to Deposit Ratio (LDR), Non Performing Loan (NPL), Loan Interest Rate, Return On Assets (ROA)